Is galectin-3 a biomarker, a player—or both—in the presence of coronary atherosclerosis?. Issue 3 (29th January 2016) - Aksan, Gökhan; Gedikli, Ömer; Keskin, Kudret; Nar, Gökay; İnci, Sinan; Yıldız, Süleyman Sezai; Kaplan, Özgür; Soylu, Korhan; Kılıçkesmez, Kadriye Orta; Şahin, Mahmut
Abstract : Atherosclerosis is a complex process mediated by leukocytes, macrophages and various inflammatory markers. Galectin-3 is secreted by activated macrophages and is involved in cardiac fibrosis, cardiac remodeling, and inflammation. The present study aimed to determine the relationship between the presence and severity of coronary artery disease (CAD) and serum galectin-3 levels. The study included 82 patients with CAD confirmed via coronary angiography and 82 healthy participants as control group. Angiographic CAD was defined as ≥50% luminal diameter stenosis of at least one major epicardial coronary artery. The severity of CAD was determined by the Gensini score; and the serum galectin-3 levels were measured via ELISA. Serum galectin-3 levels were significantly higher in the patient group with CAD than in the control group (12.96±4.92 vs 5.52±1.9 ng/mL, p<0.001). In the correlation analysis, serum galectin-3 showed significant correlation with the Gensini score (r=0.715, p<0.001), number of diseased vessels (r=0.752, p<0.001) and serum hs-CRP level (r=0.607, p<0.001). In addition, multivariate logistic regression analysis showed that the serum galectin-3 levels were significant and independent predictors of the presence of angiographic CAD (OR=3.933, 95% CI 2.395 to 6.457; p<0.001). In the present study, the serum galectin-3 levels were higher in the patients with CAD than in healthy controls. Also, serum galectin-3 levels showed a significant positive correlation with the severity of CAD. An increased serum galectin-3 level may be considered an important activator and a marker of the atherosclerotic inflammatory process in CAD.